Factorial invariance, sensitivity and differences of the measure of Anxiety, stress and depression in Brazilian workers (Research, Society and Development, 2021)
Over time the relations between negative affective dimensions, anxiety and depression have been considered important from both theoretical and mental health points of view and, therefore, constitute classic dimensions in psychology and psychopathology. The operationalization of the existing models led to the construction of measures such as the scale focus of this study, the Depression Anxiety Stress Scale (DASS) which evaluates symptoms of depression, anxiety and stress in 21 items, indicating on a four-point frequency scale how much one experienced each symptom the previous week. This is a descriptive, exploratory and correlational study with a quantitative approach involving workers in the cities of and João Pessoa-PB and Natal-RN. Considering a collection of intentional data, using the snowball method, 219 workers participated in the sample, with the majority: from the private sector (47%), from the city of João Pessoa-PB (55%), married (44%), 66% women, with Specialization (36%) and over the age of 21 years old. These workers answered the sociodemographic data and the DASS-21 scale. The results revealed that the adjusted oblique trifactor model, when compared to the other established models, presented better psychometric indicators. As well as diagnostic sensitivity for workers. The scale in question is adequate, reliable and invariable, ensuring the evaluative capacity of the construct.